Fungicidal seed treatment on germination and seedling vigour of lentil var. BINA Masur-3 - Rokib, A; Monjil, MS (Asian Journal of Medical and Biological Research, 2017)
Effectiveness of six fungicides viz., Provax-200 (Carboxin+Thiram), Bavistin DF (Carbendazim), Dithane M-45 (Mancozeb), Secure (Mancozeb+Fenamidone), Antracol (propineb) and Daconil (Chlorothalonil) were evaluated to improve seed germination and seedling vigour of lentil variety BINA Masur-3. The experiment was conducted in the Green House of Seed Pathology Centre, Bangladesh Agricultural University, Mymensingh. Positive effect of seed treatment with fungicides on seed germination and seedling vigour of lentil was recorded. At 20 DAS, increased seed germination over control was observed in treated seeds with Deconil (10.40%) and Antracol (10.00%) followed by Dithane M-45 (7.20%). Seeds treated with Deconil and Dithane M-45 produced seedlings with higher shoot length, root length and seedling vigour. At 20 DAS, higher percent increased vigour index over control was found in Dithane M-45 (24.64%) and Deconil (22.44%), respectively. Asian J. Med. Biol. Res. March 2017, 3(1): 140-144